Pelindungan Hukum Terhadap Tertanggung Atas Penutupan Polis Asuransi Jiwa Kredit Tanpa Medical Check Up (Studi Putusan Nomor 38/Pdt.G/2023/Pn Tgl) - Asyraf, Alviami Ghina; S, Sunarmi; M, Mulhadi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This scientific paper aims to analyze the **legal protection for the insured** in the context of concluding a life insurance policy for credit without undergoing a **medical check-up**. The issuance of a policy without a health examination can pose potential risks and consequences for the insured, particularly regarding the claims process in the future. This research utilizes a case study from **Decision No. 38/Pdt.G/2023/PN Tgl**, which illustrates how this practice can affect the rights of the insured. The findings indicate that while the issuance of life insurance policies for credit without a medical check-up provides convenience for clients, it also raises legal issues related to the validity of the contract and the obligations of the insurance company. The court's decision in this case study highlights the importance of legal protection for the insured and the necessity for transparency in the policy issuance process. Thus, this paper underscores the importance of a clear understanding of the rights of the insured and the need for adequate regulations to safeguard their interests within the insurance industry.